Research on Mobile Network Signaling Storm and Solution - Yanxia Xing; Congjie Mao; Jingwen Yang (Dianxin kexue)
Signaling storm has degraded the service experience of the mobile subscriber. The main reasons that leading to mobile network signaling storm were presented, and some suggestions were also given for the solution from the perspective of both terminal and network. On one hand, the signaling in the air interface can be reduced by the way of heartbeat alignment in the terminal, on the other hand, paging mechanism optimization and paging area optimization can also reduce the effect of the signaling storm. The study item of 3GPP about small data packet transmission optimization was also introduced.